INTERLAYER SHIFTS OF TWO-LAYER COMPOSITE REINFORCED PLATES AND SHELLS TAKING INTO ACCOUNT TEMPERATURE LOADS (Eureka Journal of Civil, Architecture and Urban Studies, 2025)
Combined plates and shells consisting of two layers interconnected by a pliable thin adhesive seam under the influence of external temperature loads are considered. It is found that the shear modulus and the thickness of the seam have a great influence on the strength and deformability of combined double-layer shells, especially during thermal heating.
Keywords: Combined two-layer plate and shell, interlayer shifts, temperature load, thickness of the bearing and reinforcing layer, shear stresses, shear modulus, shear function.